Role of Communication in Adaptive Mechanisms of Micro and Small Entrepreneurship for Disabled in Indonesia - Ibrahim, Fachmi; Lubis, Djuara P.; Muljono, Pudji; Sadono, Dwi (Yayasan Sinergi Kawula Muda, 2025)
People with disabilities face multiple challenges in entrepreneurship, including physical limitations, accessibility to resources, and social stigma that often hinders their business development. This study aims to explore the challenges and adaptive strategies faced by people with disabilities in entrepreneurship and identify critical factors that can support their business success. Focusing on the use of communication technology and financial support, this research examines how adaptive training and inclusive policies can influence the success of disabled entrepreneurs. The research methodology involves a literature review and data analysis from various sources to understand communication, adaptive mechanisms, micro and small entrepreneurship, and people with disabilities. Relevant data surrounding these variables were collected, summarized, and analyzed. This study underscores the pivotal role of communication in the adaptive mechanisms of micro and small enterprises operated by individuals with disabilities. Through an extensive literature review, it has been demonstrated that effective communication is essential for disabled entrepreneurs to establish robust social networks, engage with customers, and secure vital resources to address various business challenges.